The effect of phloretin on synaptic proteins and adult hippocampal neurogenesis in Aβ (1-42)-injected male Wistar rats. (23rd April 2018) - Ghumatkar, Priya; Peshattiwar, Vaibhavi; Patil, Sachin; Muke, Suraj; Whitfield, David; Howlett, David; Francis, Paul; Sathaye, Sadhana
Abstract: Objectives: Considering the deleterious effect of Aβ1-42, a study was designed to evaluate the effect of phloretin on altered synaptic proteins and adult hippocampal neurogenesis in Aβ1-42-injected Wistar rats. Methods: The rats were pretreated with 5 mg/kg p.o dose of phloretin and donepezil (positive control) for 28 days, followed by intrahippocampal injections of aggregated Aβ1-42. After termination, perfused brains were isolated and subjected to Western blot and immunohistochemistry (IHC) analysis. Key findings: The Western blot revealed that Aβ1-42-injected rats had significantly low levels of synaptophysin as compared to sham control. Phloretin pretreatment significantly protected the presynaptic protein synaptophysin against the effects of Aβ1-42. There were no significant changes in the levels of PSD95 between different groups. The IHC findings showed that Aβ1-42 significantly reduced the Ki67 and DCX in the dentate gyrus as compared to sham control. However, phloretin significantly improved the number of Ki67- and DCX-positive neurons in the dentate gyrus region as compared to Aβ1-42 group. Conclusions: This study demonstrated the protective effect of phloretin on synaptophysin and adult neuronal proliferating cells in Aβ1-42-injected rats. The encouraging findings highlight the potential of phloretin as a dietary supplement targeting key therapeutic mechanisms in neurodegenerative disorders such as AD.